Draft Annual Plan 2011-12 Orissa Volume-I - Planning Commission (Planning Commission, 2011)
Orissa, located on the east coast, is flanked by West Bengal and Jharkhand in the North, Jharkhand and Chhattisgarh in the West and Andhra Pradesh in the South. It has more than 480 km long coastline. Administratively, Orissa, has been divided into 30 districts, 58 sub-divisions, 316 tahsils, 314 blocks, 6,234 Gram Panchayats and 51,349 villages including 47,529 inhabited and 3,820 uninhabited villages.
Government of Orissa, Planning and Co-ordination Department